Comparison of Just Noticeable Differences in Localization of Virtual Sound Sources over Headphones and Loudspeakers - Dick, Sascha; Herre, Jürgen (Proceedings of the AES International Conference, 2019)
In this paper, we investigate the just noticeable difference (JND) for the perception of horizontal and vertical angular separation between rendered virtual sound source objects for combinations of different stimuli. Listening test experiments were conducted on loudspeaker and binaural headphone reproduction, to assess differences between both playback scenarios, and how closely headphone tests can approximate JNDs for loudspeaker playback. Results show JNDs in the range of 1°– 3° for horizontal separation and in the range of 7°– 22° for vertical separation for both scenarios. Differences between loudspeaker and headphone playback were found to be significant, but small in comparison to the dependence on the signal content.
herre_papers_perception_and_perception_based_signal_processing